JNK1-Mediated Phosphorylation of Bcl-2 Regulates Starvation-Induced Autophagy - Wei, Yongjie (2008)
Starvation induces autophagy to preserve cellular homeostasis in virtually all eukaryotic organisms. However, the mechanisms by which starvation induces autophagy are not completely understood. In mammalian cells, the anti-apoptotic protein, Bcl-2, binds to Beclin 1 during non-starvation conditions, and inhibits its autophagy function. Here we show that starvation induces phosphorylation of cellular Bcl-2 at residues T69, S70, and S87 of the non-structured loop, Bcl-2 dissociation from Beclin 1, and autophagy activation. In contrast, viral Bcl-2, which lacks the phosphorylation site-containing non-structured loop, fails to dissociate from Beclin 1 during starvation. Furthermore, the stress-activated signaling molecule, c-Jun N-terminal protein kinase 1 (JNK1), but not JNK2, mediates starvation-induced Bcl-2 phosphorylation, Bcl-2 dissociation from Beclin 1, and autophagy activation. Together, our findings demonstrate that JNK1-mediated multi-site phosphorylation of Bcl-2 stimulates starvation-induced autophagy by disrupting the Bcl-2/Beclin 1 complex. These findings define a mechanism that cells use to regulate autophagic activity in response to nutrient status.